Trends in the Research of Microplastics Related to Indonesia: A Bibliometric Approach - Yohanna Indriyani; Rustam Efendi (Warmadewa University Press, 2026)
Microplastic pollution has become a serious concern at the local and global levels, due to its harmful impact on the environment and living beings. This problem has also attracted attention among Indonesian researchers and has become the topic of extensive study and scientific research. A bibliometric approach has been conducted to map 328 published articles related to microplastics research in Indonesia from the Scopus database during 2010-2023, in terms of annual publication growth, research hotspots, etc. This study also presented the inventory of microplastic abundance in various terrestrial and aquatic environments in Indonesia, as a warning of how polluted our environment is by microplastics, so that it can receive greater attention. In Indonesia, research related to microplastics began to receive attention in 2016, and the year 2019 marked a higher interest in this topic. This study also revealed that microplastics studies in Indonesia mainly focused on (1) studies related to microplastics contamination (abundance, distribution, type of microplastics, etc.) in various aquatic and terrestrial ecosystems, (2) impact of microplastics on plant, animal, and human health, and (3) biodegradation of microplastics. The last topic is less studied than the other two, opening up opportunities for more intensive studies in the future. This is because Indonesia is one of the mega-biodiversity countries, which holds potential indigenous microbes and meso-fauna for microplastic degradation.